Implementación de estrategias publicitarias en los diferentes medios para fortalecer la identidad y posicionamiento de mercado del hotel playa paraíso ubicado en el km. 5 ½ vía a Data - Cruz Sánchez, Joselyn Antonella (2017)
The purpose of this thesis is to carry out an implementation of advertising strategies to achieve the positioning and growth of the beach paradise hotel in the market and to have greater impact on the user since day A day the hotel company is making great efforts to offer more And better quality services to meet the expectations of customers. In the present investigation it was observed that the beach paradise hotel during its trajectory in the market, there is a great deficit of communication and not applied a correct advertising strategy that motivates to the tourists to visit the facilities and to enjoy the services that this one offers…..